Impact factors on graduates' income and employability: an analysis at a federal higher education institution - Silva, Polyandra Zampiere Pessoa da; Chagas, Milton Jarbas Rodrigues; Lopes Júnior, Elias Pereira; Nascimento, Breno Mota do (REVISTA AMBIENTE CONTÁBIL - Universidade Federal do Rio Grande do Norte - ISSN 2176-9036, 2026)
Purpose: This study aims to analyze the influence of demographic characteristics and course evaluation on the income and employability of higher education graduates. Methodology: The research was conducted with 410 graduates of the Federal University of Cariri (UFCA) who completed their courses between 2013 and 2021. Multiple regression analysis and logistic regression techniques were used to analyze the data. Results: The results of the study reveal important data about alumni: a higher level of education was related to lower income, alumni who choose to pursue careers outside their areas of training receive higher salaries, and the perceived impact of the course is directly related to the income of graduates. Contributions of the Study: The results provide an opportunity to understand the factors that influence graduate employability and potential improvements, laying a solid foundation for further discussions and potential educational and labor market measures in the region.